Modulate the superficial structure of La2Ce2O7 catalyst with anchoring CuOx species for the selective catalytic oxidation of NH3. (1st June 2022) - Kong, Xiangchen; Li, Zhenguo; Shao, Yuankai; Ren, Xiaoning; Li, Kaixiang; Wu, Hanming; Lv, Congjie; Lv, Cheng; Zhu, Shengli
Highlights: The abundant intrinsic defects in La2 Ce2 O7 pyrochlore are beneficial to NH3 -SCO reaction. Electrostatic adsorption improves the dispersion and stability of anchoring cuo x species. The mass-transfer efficiency of surface free o is promoted by the [Ce-O-Cu] connection. The anchoring cuo x species enhance the low-temperature activity of La2 Ce2 O7 catalytic. Abstract: Air contamination caused by the ammonia slip phenomenon has gradually captured the researcher's extensive attention. An effective strategy for controlling fugitive NH3 is critical to improving the air quality and living environment. In the present work, CuO x /La2 Ce2 O7 composite as a potential candidate catalyst is synthesized through the electrostatic adsorption method for the selective catalytic oxidation (SCO) of NH3 to N2 . The 5% CuO x /La2 Ce2 O7 exhibits the best catalytic activity ( T 90 =243 ℃) and ammonia conversion efficiency. The improvement of performance is mainly attributed to the superficial connection of [Ce-O-Cu], which enhances the capturing ability of ammonia molecule and accelerates the dissociating efficiency of NH bonding for N2 evolution, simultaneously. This work provides a facile method to synthesis pyrochlore-like composite catalyst of NH3 -SCO for solving the problem of ammonia slip pollution in the future.